Production of mannitol and sorbitol from copra meal a plant design - Olano, Amparo C. (College of Engineering, 1993)
Product: analytical grade mannitol, low grade sorbitol -- Plant site: Laguna -- Annual capacity: 22,000 kg mannitol, 15,300 kg sorbitol solution -- Proposed selling price: P 2,100/kg (mannitol), P 1.30/kg (sorbitol) -- Annual gross sales: P 46,583,616.10 -- Annual net profit: P 23,984,878.20 -- Total capital investment: P 26,524,995.77 -- Total annual production cost: P 23,078,585.41 -- Payback time: 1.72 years -- Rate of return of investment: 58.16% -- Breakeven point: 1,450 kg/yr